Problems of Linguoculturological Analysis of Epics - Gaziyeva, Masmakhanım Yusif (Advances in Social Sciences Research Journal, 2022)
The article deals with the issue of linguoculturological analysis of works of fiction based on the texts of the epics "The Book of Dede Gorgud" and "Beowulf". The study addresses the analysis issues arising from the differentiation of linguistic units used in the process of describing parallel phenomena in the two epics, as a result of their connection with national culture. The differences are evident in the consumables used in everyday life, in the expression of time by different numbers. The societies described in the two epics have their own rules. In these societies, there are similarities, similarities in the behaviour of individuals performing similar tasks, in relation to the work performed. The study shows that the linguo-cultural systems identified in the process of linguo-cultural analysis of epic texts are not unambiguous. As a result, certain difficulties arise when translating them from one language to another.